Comparison of the level of organochlorine residues in paddy crops from two different cultivation practices= Perbandingan aras sisa organoklorin dalam tanaman padi daripada dua penanaman berbeza - Mohmad Sabere, Awis Sukarni; Zakaria, Zuriati; Sahid, Ismail (Penerbit UKM, 2013)
This study was conducted to investigate pesticide residues in paddy crops derived from two different types of cultivation,namely the cultural plot managed by the Malaysian Agriculture Research and Development Institute (MARDI) and the second from the farmers’ rice fields which did not follow schedules suggested by MARDI. Sample collection was carried out at post harvest. To determine the concentration of organochlorine pesticides, a gas chromatograph equipped with an electron capture detector (GC-ECD) was used. The range of pesticide residues in the leaf samples was from N/D to 579.60 ppb, in stem samples from N/D to 368.93 ppb and in the rice grain from N/D to 22.37 ppb. Some of the rice samples had levels that exceeded the standard MRL (as stipulated by WHO).